Dessiner pour repenser : valorisation d’un projet de recherche-action sur le thème de l’interprétariat en santé mentale - Stéphanie Larchanché; Daria Rostirolla (Anthropologie & Santé)
How to articulate research in medical anthropology with field practices? How to be constructively critical of these very practices? How to optimize and disseminate research results beyond the frontiers of academia? As anthropologists and mental health professionals, we present the results of an action research project led in five district mental health clinics located in Île-de-France, and whose goal was to train professionals to work with language interpreters. By resorting to humoristic illustrations drawn by one of the authors, we emphasize how humor works as a “decentering” mechanism first for the authors themselves, as well as for professionals who work in transcultural situations and who are the main target. By mindfully highlighting the critical points of this field research, we thus suggest that humor functions as an efficient transmission and awareness mechanism for translating field observations and optimizing them.